Correlating imaging parameters with molecular data: An integrated approach to improve the management of breast cancer patients. Issue 1 (February 2020) - Incoronato, Mariarosaria; Mirabelli, Peppino; Grimaldi, Anna Maria; Soricelli, Andrea; Salvatore, Marco
The goal of this review is to provide an overview of the studies aimed at integrating imaging parameters with molecular biomarkers for improving breast cancer patient's diagnosis and prognosis. The use of diagnostic imaging to extract quantitative parameters related to the morphology, metabolism, and functionality of tumors, as well as their correlation with cancer tissue biomarkers is an emerging research topic. Thanks to the development of imaging biobanks and the technological tools required for extraction of imaging parameters including radiomic features, it is possible to integrate imaging markers with genetic data. This new field of study represents the evolution of radiology–pathology correlation from an anatomic–histologic level to a genetic level, which paves new interesting perspectives for breast cancer management.